Development of Learning Media Using Articulate Storyline 3 Based on RME Approach to Increase Student's Interest in The Plane Topic at MTSS Al Karomah Berastagi - Nadya Ananda Br Sembiring; Kairuddin Kairuddin (Politeknik Kampar, 2024)
The aim of this research is to develop learning media using Articulate Storyline 3 that are valid, practical, and effective to improve students' ability to understand flat plane topics. The study was carried out at MTSS AL KAROMAH BERASTAGI. The subjects of this research were students of class VII-A. This research is research and development (R&D) using the ADDIE Model. The data collection technique uses a questionnaire assessment sheet for material experts, teaching material experts, learning practitioners and student responses. The results showed that learning media using Articulate Storyline 3 obtained an average percentage of 93.47% with the criteria of